Educational Function of the State as an Object of Administrative and Legal Regulation (Law and Safety, 2020)
The emphasis has been placed on the fact that the state has the main responsibility for the formation of state policy in the field of education and the development of effective mechanism for its implementation. The author has emphasized that without the development of effective mechanism for the implementation of the educational function of the state it will be impossible to ensure the proper functioning of all spheres of public life: political, economic, cultural, environmental, informational, law enforcement, etc. In this regard, it has been focused on the importance of clarifying the content of the educational function of the state, developing effective mechanisms for its implementation.The education has been offered to be understood as a complex process regulated by the norms of national legislation, to ensure its quality we create relevant entities, entitled to provide educational services, which allows recipients of such services to realize personal potential based on their abilities, interests, needs, motivation, capabilities and experience. It has been established that the understanding of education as the result or process is the feature of the expediency of legal interpretation of this term, since procedural issues related to the organization of the educational process, education, establishment and operation of educational institutions, education management, etc. are regulated by law, primarily by administrative law.As a result of revealing the essence of the categories “function of the state” and “education” the author has formulated own definition of the concept of “educational function of the state” as the direction conditioned by the social purpose of the state, during which the state (in the form of state and non-state subjects of educational activity) creates proper conditions to meet the needs of citizens for their intellectual, spiritual, physical and cultural development, to provide them with equal access to educational services, which, as a consequence, may lead to the achievement of the planned learning outcomes. The conclusion about the two-component purpose of the educational function of the state has been made.It has been substantiated that the implementation of the educational function of the state is mainly carried out with the help of administrative and legal tools. The characteristic features inherent in the educational function of the state as an object of administrative and legal regulation have been outlined.The author has distinguished the main prerequisites for ensuring the proper implementation of the educational function of the state: a) the existence of a coherent system of regulatory acts, the provisions of which determine the priority areas of the state educational policy and take into account European educational standards, while developing an effective mechanism for implementing regulations; b) clearly defined range of subjects of management in the field of education with the consolidation of their administrative and legal status at the legislative level; c) the system of financial and logistical support of procedures for the provision and consumption of educational services must be scientifically sound and take into account modern innovative tendencies in the education sphere; d) development of an effective mechanism for motivating the employees in the field of education to use innovative technologies.
Keywords: education; state function; educational function of the state; administrative legislation; administrative and legal regulation; mechanism of realization; subject of management in the educational sphere